FIGURE 53. A–C, E, F in Brachyuran crabs (Crustacea, Decapoda) from the remote oceanic Archipelago Trindade and Martin Vaz, South Atlantic Ocean - TAVARES, MARCOS; MENDONÇA, JOEL BRAGA DE JR. (Zenodo, 2022)
FIGURE 53. A–C, E, F, Plagusia depressa (Fabricius, 1775). A, B, Male, cl 33 mm, cw 37 mm (MZUSP 41244). C, Male, cl 35 mm, cw 39 mm (MZUSP 41247). D–F, Habitats of Plagusia depressa at Praia dos Portugueses, Trindade Island, July 2015. Photographs: (A–C) by A. Pol, (D–F) by J.B. Mendonça. Published as part of TAVARES, MARCOS & MENDONÇA, JOEL BRAGA DE JR., 2022, Brachyuran crabs (Crustacea, Decapoda) from the remote oceanic Archipelago Trindade and Martin Vaz, South Atlantic Ocean, pp. 1-129 in Zootaxa 5146 (1) on page 103, DOI:10.11646/zootaxa.5146.1.1, http://zenodo.org/record/7626155